ANALYSIS OF THE STATE OF PEDAGOGICAL WORKERS TRAINING TO USE SMART TECHNOLOGIES IN THE EDUCATIONAL PROCESS - Pryhodii, Mykola (Professional Pedagogics, 2019)
The article presents the content of the notion "SMART-complex" is defined as an interconnected set of normative and educational-methodical materials existing in the educational and educational environment of an educational institution and necessary for the effective formation of competencies as a programmed result of mastering the discipline. It is substantiated that this educational complex should be constructed on the basis of SMART-management. Based on the analysis, it is suggested: S (specification) – in accordance with the educational-professional program, clearly identify the professional and general competencies that need to be formed within the discipline and specify the program learning outcomes; M (measurability) – measure the result of the educational process on the basis of the existing knowledge and skills, the work performed (the creation of a material or ideal object); A (approachability) – to create a content library for educational discipline, a system of tasks for students in order to form individual trajectories for studying discipline, introduce elements of distance learning; R (relevance) – to reduce the time for the mastering of «secondary» information, to strengthen practical training in laboratories and workshops, to specify the content of training on the basis of a practice-oriented approach; T (time constraints) – set up intermediate stages of performance and protection of works, change time characteristics taking into account individual aspirations of students.